Analisis Kesesuaian Tujuan Kurikulum pada Buku Teks Pelajaran IPA SMP/MTs Kelas VII Semester 2 untuk Diintegrasikan dengan Materi Tsunami - Ardila Safitri; Ahmad Fauzi; Ratnawulan Ratnawulan (PILLAR OF PHYSICS EDUCATION, 2018)
Textbook lessons are one of the keys to the success and success of the implementation of curriculum 2013. Textbook lesson is one of the learning media used by teachers and students in the learning process. The material in the textbook of the lesson must be in accordance with the curriculum objectives and the material in the textbook should have local content material integrated into the textbook of the lesson. One way to judge a textbook is to analyze the textbook of the lesson. This study aims to determine the level of kissing objectives of the curriculum in science textbooks SMP / MTs grade VII semester 2 and to determine the level of conformity of scientific materials in textbook science lesson SMP / MTs class VII semester 2 with Tsunami material. There are six aspects that are assessed in terms of conformity with the curriculum that is conformity with SKL, KI, KD, scientific approach, authentic assessment and local content. Then there are three aspects that are assessed to see the appropriateness of science materials with Tsunami material is from aspects of factual, conceptual and procedural knowledge.The research type is descriptive research with qualitative approach. The sample of the data in this study was taken with the technique of Sampling Purposive, obtained textbook of science lesson of SMP / MTs VII class 2nd semester published by Kemendikbud revised edition year 2017 and textbook of science lesson of SMP / MTs class VII semester 2 endorsed by Erlangga as sample in research. The data in this study using statistical data and techniques.The findings of this study indicate that the level of kissing objectives of the curriculum of science textbooks published by Kemendikbud revised edition of 2017 is 71.2% with sufficient category and the suitability level of curriculum goals in textbooks published by Erlangga is 80.2% corresponding. Then the level of conformity of science materials in textbook science lesson of SMP / MTs class VII semester 2 with Tsunami material is 32,8% with inappropriate category.Keyword : Textbook, Analysis of conformity of curriculum objectives, Analysis of conformity of IPA materials with Tsunami materials.